Stimulasi Kemampuan Gerak Melalui Permainan Bakiak untuk Meningkatkan Artikulasi Anak Usia 5-6 Tahun di TK Kemala Bhayangkari 2 Samarinda - Adinda Nurenra Ramadhani; Heppy Liana; Yeni Aslina (BEduManagers Journal : Borneo Educational Management and Research Journal, 2025)
The Importance of Stimulating Motor Skills as a Supporting Factor in Early Childhood Language Development, Particularly in Enhancing Articulation Ability.Many children aged 5–6 years still experience difficulties in pronouncing words clearly; therefore, a fun, meaningful learning method that involves motor activities is needed. The purpose of this study is to examine the stimulation of motor skills through bakiak (traditional clog) games to improve the articulation ability of children aged 5–6 years at TK Kemala Bhayangkari 2 Samarinda, as well as to identify the forms of articulation improvement after participating in the activity. This research uses a descriptive qualitative approach with children aged 5–6 years as subjects, focusing on motor skill stimulation in improving articulation. Data were collected through observation, interviews, and documentation.The results show that motor skill stimulation through bakiak games effectively enhances children’s articulation abilities. The stimulation activities include playing bakiak four times a week for three months, which led to improved coordination between the central nervous system, muscles, and body organs. Children became more focused in coordinating body movements with word pronunciation, more confident in speaking, and able to articulate letters and syllables clearly. In addition, the bakiak game also fosters self-confidence, cooperation, and creates an enjoyable learning atmosphere. In conclusion, the bakiak game can serve as an innovative learning medium that stimulates motor skills while simultaneously improving early childhood articulation through a harmonious combination of motor and language aspects.